The pleiotropic effects of adaptogens in depression: A Systematic Review - Krężel, Maciej; Krężel, Olga; Rybińska, Marcelina; Szafraniec, Artur (Journal of Education, Health and Sport, 2026)
Depression is a condition that affects increasingly larger groups of people. It involves, among other things, disturbances in neurotransmitter function and nervous system metabolism. The reason for this condition is often an excessive amount of stimuli, according to which the brain must adapt the body to survive in changing conditions. The differences in age, race, gender, and social status that would typically identify groups at higher or lower risk of developing depression are becoming blurred. Today, depressive disorders pose a danger to the entire population. They affect people in various ways. They can result from pathological changes and processes in different systems of the body. Adaptogens, which have strong pleiotropic effects, can be used to improve the patient’s condition, well-being, and clinical status across various disorders of the entire body. These are plant-based substances that do not have as well-developed a legislative process as typical drugs on the pharmacological market. However, they play a significant role in supporting the treatment of various organ diseases throughout the body. At the same time, they alleviate neurological aberrations in the course of depressive disorders. In addition, both their antidepressant and health-promoting effects on other systems are mutually beneficial. Therefore, the use of adaptogens can benefit patients and significantly improve their quality of life during illness.